Äußerungen deutschlernender Oberschüler zum induktiven Vorgehen im Grammatikunterricht. - Hostyński, Paweł (Glottodidactica, 2001)
The article presents the outcome of empirical research devoted to inductive teaching of foreign language grammar on secondary school level. The research was carried out according to qualitative methodology with use of open interview, which allowed depicting of the issues connected with "insightful", inductive teaching from the students' perspective. Students' opinions enabled an insight into their thinking processes and views concerning certain didactic steps and stages leading to generalisations (in this case grammatical rules). Students, first of all, voice their subjective opinions on the effectiveness of the inductive approach and its influence on further language learning. Student's utterances concern also occurring problems connected with, for example, teacher's authoritative attitude, inappropriate choice of texts, unequal level of advance in the group and also involve individual hardships - internal barriers - being a consequence of attachment to the expository teaching tradition in teaching languages.